Extraction, characterization and antioxidant activity of fenugreek (Trigonella-Foenum Graecum) seed oil - Akbari, Sweeta; Nour, A. H.; R. M., Yunus; Alara, Oluwaseun Ruth; Abayomi, Olalere Olusegun (Elsevier Ltd, 2019)
Fenugreek (Trigonella-Foenum Graecum) is known as one of the traditional and most promising medicinal herbs belongs to the leguminous family. The seeds of fenugreek have been extensively studied for the treatment of inflammation, cancer and diabetes. In this study, fenugreek seed oil was extracted and evaluated for its chemical compositions and bonding through gas chromatography coupled to mass spectrometry (GC-MS) and Fourier transform infrared spectroscopy (FT-IR) analysis, respectively. The antioxidant activity against 2,2-diphenyl-picrylhydrazyl (DPPH) and 2,2′-Azino-bis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS+•) radicals, total phenolic content (TPC) and total flavonoid content (TFC) of the oil were also studied. The capacity of antioxidants detected by ABTS was stronger than that by DPPH. A total number of 23 chemical compounds were detected and identified in fenugreek seed oil comprising of 99% of the total oil through GC-MS analysis. The major compounds of the extracted oil were linoleic acid (54.13%), palmitic acid (16.21%), pinene (4.56%), 4-Pentyl-1-(4-propylcyclohexyl)-1-cyclohexene (3.87%) and linoleic acid methyl ester (3.19%). FTIR analysis confirmed the presence of carboxyl group in the oil which were more dominated by unsaturated essential fatty acids. Moreover, the oil of fenugreek seed indicated a strong antioxidant radical scavenging activity against both DPPH and ABTS assays with an IC50 of 172.6 ± 3.1 and 161.3 ± 2.21, respectively. The TPC and TFC of the oil were 38.97 ± 0.34 mg GAE/g. oil and 14.417 ± 0.23 mg QE/g.oil. Thus, this study suggests that the fenugreek seed oil could be used for pharmaceutical purposes.